Pendekatan Tipologi Tonry-Farrington dalam Upaya Pencegahan Peredaran Produk Pangan Olahan Ilegal di Wilayah Perbatasan Negara Indonesia - Yovia, Rizki Arrahman; Wibowo, Andi (Eruditio : Indonesia Journal of Food and Drug Safety, 2025)
The circulation of processed food, particularly imported unregistered products (TIE), is a significant contributor to crime vulnerability in border areas, accounting for 71% of total findings. This has become a complex issue due to its close links with the socio-economic conditions of local communities. A purely repressive approach has proven insufficient for comprehensive mitigation of this phenomenon. This study employed a mixed-methods approach, combining quantitative and qualitative methods, to examine and explain community and institutional participation, including law enforcement agencies, in addressing crime vulnerability related to processed food commodities in Indonesia’s border regions, based on the Tonry-Farrington typology. The study area covers North Kalimantan, West Kalimantan, Riau, Riau Islands, and East Nusa Tenggara provinces. The findings indicate that crime prevention using the Tonry-Farrington typology can be implemented through: (1) Developmental and Social Prevention, emphasizing crime prevention functions by engaging local key opinion leaders and traditional authorities with reputable standing to support BPOM’s efforts; (2) Community-Based Prevention, promoting collaborative approaches and resource-sharing to enhance value creation; (3) Situational Prevention, involving joint supervision and collaboration with well-informed stakeholders; and (4) Law Enforcement, advocating collaborative measures with the criminal justice system to establish strong legitimacy and a deterrent effect on offenders. The Tonry-Farrington typology can be adapted by BPOM as a novel approach to address the circulation of TIE food products in Indonesia’s border regions, enabling holistic and integrated management of crime vulnerability in these areas.